1985
DOI: 10.1055/s-2008-1059723
|View full text |Cite
|
Sign up to set email alerts
|

Anal Sphincter Function After Surgery for High Imperforate Anus - A LongTerm Follow-Up Investigation

Abstract: 37 children were treated for high imperforate anus during the years 1944-1965. Eighteen of these 37 participated in a follow-up examination at the age of 18-35 years. The examination consisted of an anorectal manometry, EMG of the external sphincter, a digital anal examination, and an interview. Special attention was paid to anal continence. Fourteen patients did not admit any major anal problems, and eight of them had a good continence. Anorectal manometry showed an absence of internal sphincter function in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…As the child grows older and matures, the interest in body functions increases, and the ability to manage the consequences of the malformation improves as well. Previous research has found that the final degree of continence in patients with high imperforate anus is achieved around puberty [27]. The higher rate of total behavioral and emotional problems found in CBCL among the children with imperforate anus cannot be disregarded.…”
Section: Discussionmentioning
confidence: 96%
“…As the child grows older and matures, the interest in body functions increases, and the ability to manage the consequences of the malformation improves as well. Previous research has found that the final degree of continence in patients with high imperforate anus is achieved around puberty [27]. The higher rate of total behavioral and emotional problems found in CBCL among the children with imperforate anus cannot be disregarded.…”
Section: Discussionmentioning
confidence: 96%
“…The contrasting clinical outcomes would support greater impairment of the ARP (median 25 cm H2O in RUF and 50 cm H2O in VF/PF) and greater shortening of the HPZ among RUF males (b1.5 cm in 40% of RUF vs 19% of VF/PF patients), consistent with more significant hypoplasia. In the literature, an association between continence and the ARP [8,21,22,24] or ASP [25] has been reported, but also the absence of a correlation with either of these [26,27]. Limitations of our study are the relatively small numbers of patients by type of ARM, and the small number of controls available.…”
Section: Discussionmentioning
confidence: 73%
“…Σν πξφβιεκα κε ηηο κεηξήζεηο απηέο ήηαλ πσο πνιιέο θνξέο νη δηάθνξεο παξάκεηξνη εκθάληδαλ αιιειεπηθάιπςε θαη πσο ηα καλνκεηξηθά επξήκαηα ήηαλ ζηαζεξά ρεηξφηεξα απφ ηελ πξαγκαηηθή θιηληθή έθβαζε θαη ιεηηνπξγία 131,140 . Οξηζκέλνη εξεπλεηέο έρνπλ βξεη ζεηηθή ζπζρέηηζε κεηαμχ ηνπ θιηληθνχ ειέγρνπ ησλ νξζνπξσθηηθψλ ζθηγθηήξσλ θαη ηεο πξσθηηθήο πίεζεο εξεκίαο 130,251 κε ηελ πίεζε ηεο εθνχζηαο ζχζπαζεο 252 ή κε ηελ παξνπζία ηνπ αλαζηαιηηθνχ νξζνπξσθηηθνχ αληαλαθιαζηηθνχ 130,251,252 . Άιινη ζπγγξαθείο δελ θαηάθεξαλ λα απνδείμνπλ θακία ζπζρέηηζε κεηαμχ ησλ καλνκεηξηθψλ επξεκάησλ θαη ηνπ ειέγρνπ ησλ νξζνπξσθηηθψλ ζθηγθηήξσλ, αθφκα θαη κε ηε ρξήζε πην ζχγρξνλσλ κεζφδσλ φπσο ε ππνινγηζηηθή αλπζκαηηθή καλνκεηξία (computerized vector manometry) 241,253,254 .…”
Section: μανομδσρηα σοτ ορθοτunclassified
“…ζαθή251,252,256,257 . ρεηηθά κε ηε ζπζρέηηζε ησλ επξεκάησλ απηψλ κε ηελ ιεηηνπξγία, ην ζεηηθφ αληαλαθιαζηηθφ έρεη ζπζρεηηζηεί κε ηθαλνπνηεηηθφ έιεγρν ησλ νξζνπξσθηηθψλ ζθηγθηήξσλ, αιιά δελ είλαη μεθάζαξν αλ νη δηαηαξαρέο απηέο νθείινληαη ζε πξσηνγελή εθθχιηζε ηνπ κπφο, λεπξνγελή βιάβε ή ηαηξνγελή βιάβε θαηά ηελ πξσθηννξζνπιαζηηθή.…”
unclassified